Time for religion thinking Christianly about religious studies in school - Hill, Brian (Sydney, NSW Australian Teachers' Christian Fellowship, 1979)
Includes bibliographical references.
Donated by the Australian Teachers' Christian Fellowship, residents of Emmaus Bible College, March 2004.
Keywords: Teaching -- religious aspects -- Christianity